2006
DOI: 10.1309/gn6qcbmlleatlk2m
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Immunohistochemical Stain Quality in Conventional and Rapid Microwave Processed Tissues

Abstract: Same-day turnaround of pathology specimens is desirable in this era of managed care, and rapid microwave tissue processing produces histologic features of a quality equivalent to overnight processing. We studied whether microwave-assisted rapid tissue processing adversely affects the quality of immunohistochemical staining. We selected 30 specimens (20 neoplastic and 10 nonneoplastic) from our routine surgical pathology workload. Paired large tissue blocks were made from each specimen type, one for microwave-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 22 publications
1
9
0
1
Order By: Relevance
“…This was similar to the findings of Hopwood D et al, [27] and Emerson LL et al, [32] who showed that malignant cells were equally well preserved by both conventional and microwave fixed tissues. Right from precancerous conditions and lesions to malignancy, reactive lesions to benign tumours, microwave technique has shown a remarkable difference without losing the architecture and morphology of the cells [23].…”
Section: Resultssupporting
confidence: 91%
“…This was similar to the findings of Hopwood D et al, [27] and Emerson LL et al, [32] who showed that malignant cells were equally well preserved by both conventional and microwave fixed tissues. Right from precancerous conditions and lesions to malignancy, reactive lesions to benign tumours, microwave technique has shown a remarkable difference without losing the architecture and morphology of the cells [23].…”
Section: Resultssupporting
confidence: 91%
“…Tumor tissues were collected, fixed in 10% buffered formalin and embedded in paraffin (27). Tissue sections were cut at 4 μm and prepared on uncharged slides.…”
Section: Histological Analysismentioning
confidence: 99%
“…Use of the microwave oven as a histological tool was introduced in the early 1990s (Leong 1996;Shin et al 2002) and involved many histological procedures such as tissue fixation, demineralization, in situ hybridization, and immunocytochemistry (Shin et al 2002;Emerson et al 2006;Tesch et al 2006). Many antibodies and conditions were tested, and the major advantage of the use of microwave technology seemed to be the speed of the procedures enabling significantly faster results in human diagnostics during surgical procedures or routine laboratory work (Cuevas et al 1994;Brown and Chirala 1995;McMahon and McQuaid 1996;Sperry et al 1996;Munoz et al 2004;Ridderstrale et al 2005).…”
Section: Discussionmentioning
confidence: 99%